409 Perioperative complications after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) – an experience from the tertiary care centre in North India. (13th November 2020) - Kumar, N; Ray, MD; Deo, S
Abstract : Introduction: In recent decades, Cytoreductive Surgery (CRS) with Hyperthermic Intraperitoneal Chemotherapy (HIPEC) has become the treatment of choice for resectable peritoneal carcinomatosis (PC). Methods: A total of one hundred eighty-eight patients underwent CRS and HIPEC from May 2014 – May 2019 and data was recorded from a prospectively maintained computerized database. Peritoneal Cancer Index (PCI), Completeness of Cytoreduction (CC), Duration of hospitalization, Postoperative morbidities and mortalities were reviewed. Morbidities were graded according to the Clavien Dindo classification. Results: Median Peritoneal Cancer Index (PCI) was 14 (range; 8–25) and completeness of cytoreduction (CC) of 0 and 1 (CC-0 and CC-1) was achieved in all patients, with CC -0 in 87 patients (90%) and CC-1 in 10 patients (10%). The median intensive care unit (ICU) was 2 days (range; 1–8 days), and the mean hospital stay was 7 days. Four (4.12%) patients died in the postoperative period. Overall 30-day morbidities after CRS and HIPEC were found in 33 patients (34%), whereas 26 patients (26%) developed Clavien Dindo major complications (III and IV). Paralytic ileus occurred in 9 patients (9%), whereas Deep Venous Thrombosis (DVT) developed in 10 patients (10%), and subacute intestinal obstruction in 11 patients (11%) in late (21–30 days) postoperative period. The most common cause of hospital re-admission was a subacute intestinal obstruction (SAIO) and managed conservatively. Conclusion: CRS & HIPEC can be performed with acceptable morbidities and mortality by experienced surgeons. Perioperative and postoperative outcomes can further be improved by proper patient selection and quality of team management.